2016
DOI: 10.3390/ijerph13030255
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Forest Therapy on Coping with Chronic Widespread Pain: Physiological and Psychological Differences between Participants in a Forest Therapy Program and a Control Group

Abstract: This study aimed to investigate the effects of a two-day forest therapy program on individuals with chronic widespread pain. Sixty one employees of a public organization providing building and facilities management services within the Seoul Metropolitan area participated in the study. Participants were assigned to an experimental group (n = 33) who participated in a forest therapy program or a control group (n = 28) on a non-random basis. Pre- and post-measures of heart rate variability (HRV), Natural Killer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(160 citation statements)
references
References 33 publications
6
117
1
1
Order By: Relevance
“…In addition, more studies suggested that the forest bathing effect on anxiety alleviation was accompanied by coniferous tree species, such as Japanese cypress (Chamaecyparis obtusa) (Lee et al 2014, Song et al 2015a, Zhang et al 2015, Song et al 2016) and pine (Pinus spp.) (Sonntag-Öström et al 2015a, b, Chun et al 2016, Han et al 2016). However, very little evidence can be found about the perceived anxiety by participants in the birch forest.…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, more studies suggested that the forest bathing effect on anxiety alleviation was accompanied by coniferous tree species, such as Japanese cypress (Chamaecyparis obtusa) (Lee et al 2014, Song et al 2015a, Zhang et al 2015, Song et al 2016) and pine (Pinus spp.) (Sonntag-Öström et al 2015a, b, Chun et al 2016, Han et al 2016). However, very little evidence can be found about the perceived anxiety by participants in the birch forest.…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 98%
“…Given the fact that the tree species in our study were broad-leafed, we consider that there may exist some tree-species significance in the effect of forest bathing on perceived anxiety alleviation. Although few studies have focused on this issue, studies about forest bathing suggested that the significant effect on mental restoration also accompanied by hard-wood species of oak (Park et al 2007, Lee et al 2009, Han et al 2016) and maple (Lee et al 2014, Song et al 2015b, Han et al 2016). In addition, more studies suggested that the forest bathing effect on anxiety alleviation was accompanied by coniferous tree species, such as Japanese cypress (Chamaecyparis obtusa) (Lee et al 2014, Song et al 2015a, Zhang et al 2015, Song et al 2016) and pine (Pinus spp.)…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 99%
See 1 more Smart Citation
“…For articles published in English, nine studies [12,19,21,22,25,28,29,34,39] used POMS to assess the level of depression and three studies [28,29,39] used Semantic differential (SD) method. Other scales used by the studies included the Hamilton Rating Scales for Depression [20], Beck Depression Inventory (BDI) [16,20,24,31], positive and negative affect schedule (PANAS) [34]. For studies published in Korean, the POMS [15,23,26,27,32,38] and BDI [13][14][15]17,18,35] were the most commonly used scale.…”
Section: Depression Measuresmentioning
confidence: 99%
“…Other scales used to measure depression were the Hospital Anxiety and Depression Scale (HADS) [38], Hamilton Rating Scales for Depression [17], Montgomery-Asberg Depression Rating Scales [17], Symptom Check List (SCL-90-R) [32], and Zung Self-Rating Depression Scale (SDS) [36]. Fourteen studies [13,15,[17][18][19][21][22][23][24][25][26]28,29,39] used both self-report, paper-and-pencil questionnaires, and physiological measures, while 14 studies [12,14,16,20,27,[30][31][32][33][34][35][36][37][38] used only selfreport, paper-and-pencil questionnaires. Physiological or objective measures included heart rate variability (HRV), blood pressure, heart rate, and amylase concentration.…”
Section: Depression Measuresmentioning
confidence: 99%